Experiments in the purification and characterization of enzymes : - Crowley, Thomas E (Elsevier, 2014)
Experiments in the Purification and Characterization of Enzymes: A Laboratory Manual provides students with a working knowledge of the fundamental and advanced techniques of experimental biochemistry. Included are instructions and experiments that involve purification and characterization of enzymes from various source materials, giving students excellent experience in kinetics analysis and data analysis. Additionally, this lab manual covers how to evaluate and effectively use scientific data